E-LKPD Pada Materi Sistem Persamaan Linear Dua Variabel Dengan Konteks Moderasi Beragama: Kepraktisan Pada Tahap Small Group - Vidiya, Eling Che (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2023)
This research is a development research, and in developing interactive E-Worksheet using Tessmer development model. The product in this study is E-Worksheet on system of linear equations in two variables material with the context of religious moderation that has been developed by researchers. The research subjects used were VIII grade students of SMP Muhammadiyah 1 Palemban as many as 6 students. This research has passed the product validation test by 4 validators consisting of media, material, language and context aspects at the expert review stage. In addition, it has also passed the validity test and item reliability test. After being declared valid, the practicality test stage was continued. The main focus of this research is to discuss practicality at the small group stage.  This is in line with the purpose of the study which is to find out the Interactive E-Worksheet that is practical at the small group stage. The data collection techniques used were questionnaires and interviews. The data analysis techniques in this study are questionnaire analysis of practicality and analysis of interview results both quantitatively and qualitatively. The results of this study are E-Worksheet on system of linear equations in two variables material with religious moderation context from the aspect of effectiveness with a percentage of 88.15%, attractiveness of 89.33% and implementation of 88.89% with very practical criteria.